Combination of dexmedetomidine and esketamine for postoperative nausea and vomiting in patients undergoing laparoscopic surgery: study protocol for a prospective, randomized, controlled trial - Ying Zhou; Ziyi Shen; Jinbiao Li; Hui Cao; Xinggen Zhou; Weicheng Jin; Ming Yao; Jing Chi; Jie Wang; Chao Zhang (Trials)
Abstract Background Laparoscopic surgery has gained widespread acceptance due to its advantages over traditional open procedures, including less postoperative pain and faster recovery. However, postoperative nausea and vomiting (PONV) remains a prevalent complication, affecting up to 80% of high-risk patients and significantly reducing patient satisfaction and recovery quality. Although opioids are frequently used for intraoperative analgesia, their side effects, particularly PONV, highlight the need for opioid-sparing strategies. Dexmedetomidine and esketamine are two agents with analgesic and anesthetic-sparing properties that have shown promise individually in reducing PONV and postoperative pain. However, evidence remains limited, and no study has systematically evaluated the combined use of dexmedetomidine and esketamine for PONV prevention in laparoscopic surgery. This trial aims to fill this knowledge gap by assessing the efficacy and safety of this novel combination strategy, potentially offering an improved anesthetic regimen for enhanced postoperative recovery. Methods To address this gap, we propose a prospective, randomized, controlled trial (RCT) at a single center to evaluate the effects of dexmedetomidine and esketamine on PONV in laparoscopic surgery patients. Patients will be randomly assigned to either the combination therapy group or the control group in a 1:1 ratio. The combination therapy group (n = 70) will receive intravenous dexmedetomidine (0.5 μg/kg), esketamine (0.3 mg/kg), sufentanil (0.2 μg/kg) and propofol (1.5–2.0 mg/kg) for anesthesia induction, with sevoflurane (2–3%) used for maintenance during surgery. Conversely, the control group (n = 70) will receive sufentanil (0.5 μg/kg) and propofol (1.5–2.0 mg/kg) for anesthesia induction, followed by sevoflurane (2–3%) inhalation and continuous remifentanil infusion (0.1 μg/kg/min) for maintenance. The primary outcome is the incidence of PONV within 48 h postoperatively, assessed during three predefined intervals: 0–6 h, 6–24 h, and 24–48 h. Secondary outcomes include Apfel PONV risk score, pain scores at 0, 6, 12, 24, and 48 h postoperatively, time to first PONV episode and first rescue antiemetic, time to first rescue analgesic, total dosage and frequency of rescue analgesics and antiemetics within 48 h, patient satisfaction score at discharge, length of hospital stay, discharge condition, and the incidence and classification of adverse events. Discusssion This study aims to evaluate the safety and feasibility of combining dexmedetomidine and esketamine to prevent PONV in patients undergoing laparoscopic surgery. The findings may offer evidence for an effective opioid-reducing anesthesia strategy that enhances analgesia and supports recovery, with potential value for broader clinical application. Trial registration {2a,2b} Chinese Clinical Trial Register, ChiCTR2300072455. Registered on June 14, 2023.